Exploration of Pedagogical Approaches during the Buddhist Era (Rupandehi Campus Journal, 2024)
This research article explores the education system prevalent in ancient India during the era of the Buddha. The study aims to provide a comprehensive understanding of the teaching methods employed during that time and elucidate various facets and dimensions of teaching practices. The article examines insights gleaned from Buddhist literature and scriptures, focusing on the Buddha’s innovative and impactful teaching methods such as sermons, parables, and interactive exchanges. It also explores the pedagogical approaches of Buddhism, highlighting the egalitarian nature of Buddhist education and its inclusivity of individuals from all social backgrounds. The article discusses different teaching methods employed during the Buddhist era, including the Shravan method, imitation method, demonstration and practice method, interpretation method, lecture method, debate and logic method, seminar, conference and Shāstrārtha method, self-study method, and excursion method. The research article concludes by highlighting the enduring relevance of the teaching methods from the Buddha’s era in enriching the ancient culture and fostering a moral and virtuous society.